Synthesis of polyaniline-montmorillonite nanocomposites using H2O2 as the oxidant - Narayanan Binitha; Viswanathan Suraja; Zahira Yaakob; Sankaran Sugunan (Universiti Kebangsaan Malaysia, 2011)
Polyaniline montmorillonite nanocomposite was prepared using H2O2 as the oxidant. The catalytic environment of montmorillonite favours polymerization. Intercalation and composite formation was proven from various techniques such as XRD, FTIR, DRS and thermal analysis. XRD patterns give the dimension of the intercalated PANI, from the shift of 2θ values, which is in the nano range. FTIR showed that PANI composite formation occured without affecting the basic clay layer structure. Thus the successful development of an alternative cheap route for polyaniline–montmorillonite nanocomposite was well established.